The Relationship between Social Support and the Participation of Mothers of Toddlers in the Stunting Prevention Program in Medan City - Sri Hajijah Purba; Nirma Juli Saputri (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Stunting is a form of growth and development failure in toddlers that results in linear growth disorders, namely from in the womb to the age of two years. North Sumatra has several districts or cities that are the focus of stunting control locations, one of which is Medan City. The prevalence of stunting in Medan City in 2020 was 11.69% and increased in 2021 to 19.9% but in 2022 it fell again to 15.4%. Stunting can be overcome by carrying out specific nutritional interventions by involving the role of mothers of toddlers in the stunting control program. The purpose of this study was to analyze social support such as community leaders, cadres, and families that influence the role of mothers of toddlers in the stunting control program in Medan City. The type of research used is quantitative research with a cross-sectional research design. The population in the study were all mothers who had toddlers with stunting in Medan City. The sampling technique was Random Sampling. The research sample was 257 mothers of toddlers. The data collection technique used a questionnaire. The data analysis of this study used the Chi-Square test. The results showed that as many as 198 (77%) mothers of toddlers had low participation in the stunting control program, while as many as 59 (23%) had high participation. The social support factor (p-value = 0.739 > 0.05) did not affect the participation of mothers of toddlers in the stunting control program. Social support significantly affects the participation of mothers of toddlers in stunting control in Medan City, so it is necessary to increase family involvement and cadre communication. Keyword: Stunting, Participation, Support, Social, Family